Modelling Study Ol High-Current Density Chlorophyll-Based Dyesensitized Solar Cell - Abdul Akram Azfar, Abd Fadzir (2022)
Due to its low cost of production, the dye-sensitized solar cell (DSSC) has sparked a lot of attention. Many studies have been conducted to improve its features and structure for optimal efficiency and fill factor. In this paper, 10 samples of chlorophyll dye, Neem leaves, Apricot leaves, Papaya leaves, Pawpaw leaves, Scent leaves, Spinach, Ti plant leaves, Morning Glory leaves, Jatropha Curcas leaves and Chinar leaves are used in order to find the highest current density-voltage (J-V) by using General-purpose Photovoltaic General-purpose Photovoltaic Device Model (GPVDM) software. Different types of chlorophyll dye have their own parameters where they produce different output of J-V. In order to finding the main parameter that can produce the highest J-V, GPVDM is used by simulate all samples chlorophyll dye. In GPVDM, there are two main critical data are needed before inserting the dye material; absorbance data and refractive index data of the material. The electrical simulation has been made by using GPVDM which are using the different size of active area DSSC by referring to the previous research paper. Spinach dye is producing the highest simulated J-V compared to the other samples with 1.6 mA/cm2.